Influence of healthcare institution managers' proactive approach to communication activities on patient satisfaction - Filipović Vinka; Cicvarić Slavica; Štavljanin Velimir; Damnjanović Vesna; Radojičić Zoran; Žarkić-Joksimović Nevenka; Gogić Aleksandra (Vojnosanitetski Pregled)
Background/Aim. Over the recent years customer satisfaction program as a tool for patient satisfaction has been recognized as an important issue in healthcare services. The aim of this preliminary study was to explore an influence of healthcare institution managers' approach and attitudes to marketing and public relations activities (communication activities), in the context of implementation of customer satisfaction programs, on patient satisfaction. Methods. The study was conducted among managers from different state-owned healthcare institutions (healthcare centers, clinics, hospitals) in Serbia. The structured questionnaire form, comprising both open and closed questions, was used as a main research tool. The total number of sent questionnaires was 120; 56 questionnaires were sent back, while 49 of them were valid. Results. It was shown that 42.9% of healthcare institutions apply proactive media approach, and that 35.7% of the organizations have a person who, besides his/her basic engagements, performs activities connected with marketing and public relations. Using Chi-square likelihood ratio test it is confirmed that these activities have a significant role in supporting customer satisfaction program implementation (p < 0.05). The results showed that in 69.4% cases, positive attitude of healthcare institutions managers toward marketing and public relations activities had positive influence on patient satisfaction (p < 0.05). Conclusion. Managers in healthcare sector in Serbia who used proactive approach toward media and who had already institutionalized communication activities with external stakeholders have a positive attitude to implementation of customer satisfaction program. Furthermore, managers' attitude toward communication activities has influence on patient satisfaction.